Lucerne meal in the diet of indigenous chickens: a review - Ginindza, Muzi M. (Frontiers in Animal Science, 2023)
Indigenous chicken production consists of an array of activities important to smallholder poultry farmers in Africa. One of the many activities influencing their production and threating the local food security is in the area of nutrition, particularly, protein supplementation. The available feed resources to farmers are not enough to sustain productivity of chickens. Hence, their diets often require nutritional supplementation. Validation of locally grown feed ingredients is, therefore, an urgency for improving sustainability of poultry production in Sub-Saharan Africa. A dietary ingredient that may be used in the diets of chickens is lucerne (Medicago sativa) also known as alfalfa. In South Africa, lucerne is the most cultivated forage legume and about 1.3 million metric tonnes of lucerne are produced per year. Lucerne has high nutritional value, as source of protein, amino acids, vitamins as well as fatty acids. The potential of lucerne as a feed resource for indigenous chickens should be, therefore, investigated to develop strategies to improve the nutrition of such chickens. The purpose of this review was to highlight lucerne as a potential dietary ingredient for indigenous chickens and discuss its effects on productivity of broilers, egg-layers and dual-purpose.